Reprodutibilidade do teste do degrau de chester em pacientes com doença pulmonar obstrutiva crônica - Oliveira, Aline Nogueira de (2009)
The chronic obstructive pulmonary disease (COPD) produces dysfunction on peripheral skeletal muscles and damage on the physical capacity. The clinical field tests that avalue the capacity to exercise are important tools to the follow up of patients with COPD. Among the most utilized tests the out standings are: six-minute walk test, shuttle test and, most recently the step test. The objective of this study was to evaluate the reproducibility of the step test of Chester step test (CST) in patients with chronic obstructive pulmonary disease. Fourteen patients were studied (12 males) with stable COPD (FEV1 38,3  12,6 % of predicted). The patients performed two CST (48 hours apart). The total number of step, heart rate, peripheral oxihemoglobin saturation and perception of symptoms (dyspnea and fatigue lower limbs) obtained on the two CST presented good to excellent reproducibility. It was observed a significant correlation between the total number of steps and the heart rate measured at the peak of the test. In conclusion, the Chester step test is a reproducible test, and it can be an additional tool to evaluation for patients with COPD.